2021
DOI: 10.1186/s12935-021-02394-w
|View full text |Cite
|
Sign up to set email alerts
|

SYT7 acts as an oncogene and a potential therapeutic target and was regulated by ΔNp63α in HNSCC

Abstract: Background Head and neck squamous cell carcinoma (HNSCC) are one of the most common types of head and neck cancer, and it is urgent to find effective treatment for advanced patients. Exploring developing and progressing mechanisms of HNSCC could provide a theoretical basis to find new therapeutic targets. Methods In our research, we performed a whole-gene expression profile microarray analysis to identify differential expression genes between squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Double knockdown of FBXW7 and circ_RNF13 partially rescued the reduction of TRIM24 and DDX27. Partial rescue effects by double knockdown have also been reported in previous studies [ 33 , 34 ]. Our findings suggest that FBXW7 might not be the only downstream effector of the circ_RNF13/TRIM24/DDX27 axis.…”
Section: Discussionsupporting
confidence: 80%
“…Double knockdown of FBXW7 and circ_RNF13 partially rescued the reduction of TRIM24 and DDX27. Partial rescue effects by double knockdown have also been reported in previous studies [ 33 , 34 ]. Our findings suggest that FBXW7 might not be the only downstream effector of the circ_RNF13/TRIM24/DDX27 axis.…”
Section: Discussionsupporting
confidence: 80%
“…Syt7 is significantly upregulated in non-small cell lung cancer, thyroid cancer, and HNSCC [15][16][17]. Increased Syt7 promotes cancer cell proliferation and inhibits cancer cell apoptosis [15][16][17]. Syt7 interacts with BRCA1 to suppress the ubiquitination of HMGB3, which contributes to the role of Syt7 in thyroid cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…In the autonomic nervous system, Syt7 has been identified expressed in the sympathetic nerve terminals, regulates Ca 2+ ‐dependent norepinephrine (NE) exocytosis and enhances Ca 2+ ‐independent NE overflow [14]. Besides, Syt7 has been demonstrated to mediate several tumorigenesis such as lung cancer [15], thyroid cancer [16], and head and neck squamous cell carcinoma (HNSCC) [17]. Recent advance has revealed that Syt7 participates in vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that ΔNp63α could affect HNSCC cells by downregulating the expression of SYT7 in vitro , including inhibiting proliferation, promoting apoptosis, and reducing the proportion of cancer cells in G1 phase. Therefore, the ΔNp63α/SYT7 axis might be a potential clinically effective target for the treatment of HNSCC ( 29 ).…”
Section: Roles Of Synaptotagmin Family Members In Cancersmentioning
confidence: 99%